2009
DOI: 10.1007/s10615-009-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Mothers’ Perceptions of Reactive Attachment Disorder Therapy and its Impact on Family Functioning

Abstract: The purpose of this qualitative study was to explore adoptive mothers' perceptions of attachment therapy and its impact on family functioning. Sixteen mothers were interviewed 3 years after therapy. Analysis of the data revealed two sets of parental perceptions: first, attachment therapy was consistently supportive, emotionally painful, and physically safe; second, therapy preserved family structure, mothers remained committed to their children, and parenting was continuously stressful. This study highlights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…The STAI data supports research by Wimmer, Vonk and Reeves [16], who found that Attachment Therapy provided to adoptive families in Georgia through post-adoptive services provided mothers with hope and a sense of support, reducing feelings of anxiety. Our camp study suggested that just coming to camp reduced anxiety.…”
Section: Who Comes To the Camp And What Are The Key Issues?supporting
confidence: 83%
“…The STAI data supports research by Wimmer, Vonk and Reeves [16], who found that Attachment Therapy provided to adoptive families in Georgia through post-adoptive services provided mothers with hope and a sense of support, reducing feelings of anxiety. Our camp study suggested that just coming to camp reduced anxiety.…”
Section: Who Comes To the Camp And What Are The Key Issues?supporting
confidence: 83%
“…Sustained social withdrawal is expected, almost by definition, to be frequently observed in institutions for babies and toddlers, where significant environmental deprivation and insufficient stimulation are common (Kreppner et al., ; van IJzendoorn et al., ). For some institutionalized infants, social withdrawal may be a coping strategy and may be associated with autistic‐like behaviors observed among these children (Castle et al., ) as well as reactive attachment disorder (Zeanah et al., ), which is frequently diagnosed in adopted children (Wimmer, Vonk, & Reeves, ). In some of the cases, sustained withdrawal may be a symptom of reactive attachment disorder.…”
Section: Sustained Social Withdrawal Among Adopted Infantsmentioning
confidence: 99%
“…Welcoming an adoptive child into the family is very different than giving birth to a child as the majority of international adoptions occur after infancy, and the critical milestone of developing attachment to a caregiver may have been stalled by the early deprivation. Many authors note that by the time the adoption is finalized, adoptive parents are eager to claim their child, wanting to bond with him or her immediately (Shapiro et al, 2001;Welsh et al, 2007;Wimmer et al, 2010). However, depending on the child's early experiences with caregivers, he or she may actively push the adoptive family away, withdraw from them, or become aggressive toward them (Shapiro et al, 2001).…”
Section: The Task Of Attachmentmentioning
confidence: 99%
“…However, depending on the child's early experiences with caregivers, he or she may actively push the adoptive family away, withdraw from them, or become aggressive toward them (Shapiro et al, 2001). Thus, there may be a mismatch between the adoptive parents' readiness to attach and the child's inability or unwillingness to do so (Shapiro et al, 2001;Wimmer, Vonk, & Reeves, 2010). Research has shown that there is a significant relationship between the child's ability to attach and the adoption outcome, with the adoptee's capacity for attachments being a strong protective factor for adoptive families (Adoption Institute, 2010).…”
Section: The Task Of Attachmentmentioning
confidence: 99%
See 1 more Smart Citation